PENGARUH ISLAMIC CORPORATE GOVERNANCE TERHADAP EARNING MANAGEMENT PADA PERBANKAN SYARIAH - Annisaa, Restu Hanin; Rizki, Tabah (UNIVERSITAS DHARMAWANGSA, 2025)
This study aims to examine the effect of Islamic corporate governance (ICG) on earnings management. Earnings management variables are measured using discretionary accruals and ALLP. ICG in this study covers two categories, namely Sharia Governance (SG) and General Governance (GG). This study uses a sample of Islamic commercial banks registered with the financial services authority. The sampling technique used is purposive sampling. The research sample consists of 9 companies with a total of 81 data points. The data analysis technique used in this study is Partial Least Square Structural Equation Model (PLS-SEM) using Smart PLS version 4.0 software. The results show that ICG has a significant negative effect on earnings management.